2004
DOI: 10.1002/chin.200425005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation on the Relative Stability of the PdS2‐ and Pyrite‐Type Structures of PdSe2.

Abstract: Structure Structure D 2000Experimental and Theoretical Investigation on the Relative Stability of the PdS 2 -and Pyrite-Type Structures of PdSe 2 . -Energy-dispersive XRD at room temperature reveals that PdSe2, crystallizing in the orthorhombic space group Pbca with Z = 4 at ambient pressure, undergoes a reversible structural transition from the PdS2-type to the pyrite-type structure at a pressure around 10 GPa. The observed pressure-induced structural changes are characterized by DFT and extended Hueckel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…1). [4][5][6]26] Raman spectra suggest that the PdS2-type and pyrite-type phases coexist in the intermediate pressure range. [4][5][6] Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1). [4][5][6]26] Raman spectra suggest that the PdS2-type and pyrite-type phases coexist in the intermediate pressure range. [4][5][6] Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1. Experimental lattice constants are a = 5.7457, b = 5.8678, and c = 7.6946 Å [23], and in our work the lattice vectors a, b, and c are along the x, y, and z axes, respectively. We construct atomic structures of monolayer and bilayer PdSe 2 by cutting the bulk atomic structure and including a large enough vacuum region of about 20 Å.…”
Section: A Atomic Structuresmentioning
confidence: 83%
“…1(a), where triple layers are separated by 2.40 Å. Atomic positions are from experimental values [23]; that is, one of the Pd atoms is at (0, 0, 0), and one of the Se atoms is at (0.11125, 0.11799, 0.40573) in terms of fractional coordinates with respect to lattice vectors, and other atomic positions are determined by symmetries.…”
Section: A Atomic Structuresmentioning
confidence: 99%
“…Many previous studies have shown that one can tune the electronic and optical properties of the TMDs by applying mechanical strains [2,16,17,[20][21][22]. Although the optical properties of the monolayer PdS2, electron transport properties and stability of the bilayer and bulk PdS2 have been studied in references [2,23,24], there are very few studies on the first principles analysis of the orthorhombic PdS2. It is a need of analysis for the optical and piezoelectric properties of the orthorhombic PdS2 under strains with different magnitudes.…”
Section: Hementioning
confidence: 99%